Comparison of Laravel and Symfony - the most popular PHP frame-works, based on a simple CRUD application - Gajewski, Patryk; Dzieńkowski, Mariusz (Journal of Computer Sciences Institute, 2024)
The main purpose of the study is to compare the performance of two popular PHP language programming frameworks - Laravel 10 and Symfony 6 based on test CRUD-type applications. The benchmarking also considered the implementation process and support from the development community. The study was conducted using two simple and small test applications with the same sets of functionality. Performance was measured based on the execution times of single CRUD-type operations and handling dozens and hundreds of requests simultaneously. Execution times were measured via the Postman application from when the request was sent to the server until the response was received. The results showed that Symfony 6 is a better solution for applications where performance matters.